2017
DOI: 10.1177/1708538117741764
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress And Prolidase Enzyme Activity In The Pathogenesis Of Primary Varicose Veins

Abstract: Objectives Vascular endothelial dysfunction leads to the emerging of free oxygen radicals, deficiency of antioxidant system, forming of oxidative stress, inflammatory processes and release of proinflammatory cytokines. These things play big role in the development of primary varicose veins. Prolidase has been reported as an indicator of oxidative stress in diabetes, diabetic neuropathy, non-ulcerous dyspepsia, osteoporosis, polycystic over syndrome and many other diseases. The aim of this study is to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Increased miR‐202 expression has been shown to induce oxidative stress via Oct1 modulation . Oxidative stress presents as venous insufficiency and plays a role in the development of primary varicose veins . We found that PGC‐1α was linked to the inhibition of ROS production induced by miR‐202 mimic.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Increased miR‐202 expression has been shown to induce oxidative stress via Oct1 modulation . Oxidative stress presents as venous insufficiency and plays a role in the development of primary varicose veins . We found that PGC‐1α was linked to the inhibition of ROS production induced by miR‐202 mimic.…”
Section: Discussionmentioning
confidence: 75%
“…28 Oxidative stress presents as venous insufficiency and plays a role in the development of primary varicose veins. 43 We found that PGC-1α was linked to the inhibition of ROS production induced by miR-202 mimic. Moreover, PGC-1α is a critical modulator of the inflammatory response.…”
Section: Discussionmentioning
confidence: 80%
“…Gray et al reported the “complete absence of valves in the large communicating veins” in a 40‐year‐old woman with prolidase deficiency (Gray et al, 1983). Interestingly, the prolidase enzyme has been implicated in the pathogenesis of varicose veins (Akar et al, 2018). In addition to the detection of a disruptive variant within the PEPD gene, the diagnosis was confirmed by a markedly elevated proline level in the patient's urine.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that the dysfunction of the vascular endothelium might be the result of an excessive generation of ROS, depletion of antioxidant defenses, and the development of oxidative stress [ 8 ]. Eventually, the oxidative stress progresses to CVD, creating a vicious circle.…”
Section: Introductionmentioning
confidence: 99%